Picture Story Books as a Medium to Improve Analytical Skills in Islamic Religious Education Learning at SMP Negeri 2 Meulaboh - Ramadhaniati; Jujanna, Putri (Jurnal Profesi Guru Indonesia, 2025)
This study aims to examine the effectiveness of picture storybooks as a learning medium to enhance students’ analytical skills in Islamic Religious Education at SMP Negeri 2 Meulaboh. The research employed Classroom Action Research (CAR) conducted in two cycles, each comprising planning, action, observation, and reflection stages. The research subjects were 30 eighth-grade students. Data were collected through analytical skill tests, observation sheets, and interviews. Results showed a significant improvement in students' analytical abilities following the intervention. In the preliminary stage, only 46.7% of students achieved the minimum mastery criteria. This increased to 70% in Cycle I and reached 86.7% in Cycle II. The data indicate that picture storybooks are effective in stimulating critical and reflective thinking, particularly in interpreting moral messages, drawing conclusions, and linking religious stories to real-life situations. The visual narrative elements of the media encouraged student engagement and supported group discussions, making the learning experience more meaningful. Thus, picture storybooks can be considered a viable alternative learning strategy to develop higher-order thinking skills in religious education, especially in environments with limited access to digital tools.